Customary Law In Indonesia: A Legacy for a Sustainable Future - Surjanti, Surjanti; Sari Dewi , Retno; Pangestuti, Erly; Eko S, Bambang Slamet (CV. Era Digital Nusantara, 2025)
This article explores the relevance of customary law in fostering a sustainable future. Customary law, rooted in the traditions and values of indigenous communities, offers valuable insights and practices for addressing contemporary challenges such as environmental degradation, social inequality, and economic disparity. We will examine how customary law, with its emphasis on community well-being, environmental stewardship, and social justice, can provide a framework for sustainable development. The presentation will delve into specific examples of how customary law has been successfully applied in various contexts, highlighting its potential to contribute to a more equitable and sustainable future for all.